(untitled) (UNED Research Journal, 2019)
Introduction: Integrated efforts for the management and conservation of natural resources require the availability of socio-cultural information. However, perceptional studies are rarely used along with biological data to design methodologies of biodiversity conservation. Objective: To explore the potential of perceptional information on fungi as a tool for developing culture-sensitive methods of management and conservation. Methods: Through a survey-based design, ethnomycological information from urban settings in Honduras and Costa Rica was collected and evaluated for a group of young adults (16-25 years old, N=615 surveys). Results: Fungi were not perceived to have the value of plants and animals, in both countries. The latter were mentioned as preferred by 74% of respondents. By country, 39% of Costa Ricans mentioned the most important use of fungi to be food, whereas 58% of Hondurans responded a medicinal application. Remarkably, 27% of respondents in Costa Rica mentioned that fungi are important in ecological processes, much higher than Hondurans with only 7%. Conclusions: Exposure to formal education or previous cultural background may not play such an important role in shaping perceptions of the group of fungi as it does social aspects associated with the city lifestyle in the populations studied.